Barriers and enablers to consumer and community involvement in research and healthcare improvement: Perspectives from consumer organisations, health services and researchers in Melbourne, Australia. (15th July 2021) - Ayton, Darshini; Braaf, Sandra; Jones, Angela; Teede, Helena; Gardam, Madeleine; Bergmeier, Heidi; Skouteris, Helen
Abstract: Partnering with consumers and patients and the community and public is a research and healthcare improvement imperative. Consumer and community involvement (CCI) requires behaviour change at the individual (researcher, health professional, manager), organisational (health service, university, medical research institute) and system level (funding policies, collaboration between organisations). To understand the barriers and enablers to meaningful CCI, a qualitative descriptive study was undertaken with researchers, health professionals, representatives from consumer organisations, and health services and ethics committees in Melbourne, Australia. Twenty‐eight semi‐structured interviews and one focus group were conducted in May–August 2019. Ethics approval was obtained. Thematic analysis was guided by the Capability, Opportunity and Motivation and Behaviour model (COM‐B). Training of researchers and health professionals in CCI, benefits and systems and processes to undertake CCI, alongside incorporating CCI as a requirement for funding were identified as enablers. Lack of time and resources for CCI, challenges in finding consumers for projects and a perceived lack of evidence of the impact of CCI were barriers. These identified barriers and enablers will inform strategies to build the capacity of CCI at the individual, organisation and system level within the Australian Health Research Alliance.